Uterocutaneous Fistula Complicating Caesarean Section: A Case Report - Akiseku AK; Popoola MA; Olatunji AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
A uterocutaneous fistula (UCF) is a rare clinical presentation following Caesarean section (CS) and other pelvic surgeries. Presently, there are limited reports on the clinical management of UCF. This report describes a 35-year-old woman who presented with a four-year history of abdominal pain and cyclical bleeding from the skin after CS. Fistulography was carried out, and a diagnosis of UFC was made. She had a fistulectomy with the fistula tract excised, followed by debridement of the necrotic tissue and repair of the uterus. At the third-month postoperative follow-up, there was no recurrence of symptoms. A UCF is a rare condition that needs detailed investigation and timely medical and surgical management.